A new well structure and methane recovery enhancement method in two coal seams. Issue 16 (17th August 2020) - Wang, Chao-Wen; Jia, Chun-Sheng; Peng, Xiao-Long; Zhu, Su-Yang; Liu, Feng
ABSTRACT: The methane from two coal seams are usually produced in the same production well, and the commingled production process is of low efficiency. In order to enhance the methane recovery from the two coalbeds, a 'multi-branch U-shaped' well is introduced to double-coal seams. This well structure can perform a single layer or commingled production. There are at least 10 production methods for the new well: (1) Drainage gas recovery of upper coal seam, (2) gas injection huff and puff of upper coal seam, (3) gas injection displacement of upper coal seam (including continuous gas injection or intermittent gas injection), (4) drainage gas recovery of lower coal seam, (5) gas injection huff and puff of lower coal seam, (6) gas injection displacement of lower coal seam (including continuous gas injection or intermittent gas injection), (7) drainage gas recovery of both coal seams, (8) gas injection huff and puff of upper coal seam and drainage gas recovery of lower coal seam, (9) gas injection huff and puff of lower coal seam and drainage gas recovery of upper coal seam, and (10) gas injection displacement of both coal seams. Meanwhile, five production strategies are investigated by simulations with reference to the special well structure. Combined with the coalbed methane field operation, the well is conducive to carbon dioxide huff and puff, the optimized production strategy is: water drainage in the early period, and carbon dioxide huff and puff at middle-late stages of development. The new well structure can greatly improve CBM recovery.